Challenges and opportunities in bioimage analysis - Li, Xinyang; Zhang, Yuanlong; Wu, Jiamin; Dai, Qionghai (Nature methods, 2023)
Advanced imaging techniques provide holistic observations of complicated biological phenomena across multiple scales while posing great challenges to data analysis. We summarize recent advances and trends in bioimage analysis, discuss current challenges toward better applicability, and envisage new possibilities.